A Human 3D In Vitro Model to Assess the Relationship Between Osteoporosis and Dissemination to Bone of Breast Cancer Tumor Cells. Issue 7 (5th January 2017) - Salamanna, Francesca; Borsari, Veronica; Brogini, Silvia; Torricelli, Paola; Cepollaro, Simona; Cadossi, Matteo; Fini, Milena
Abstract : Despite consistent improvements in diagnostic and therapeutic strategies for breast cancer, up to 40% of patients will develop bone metastases. To reduce the morbidity and complications related with bone metastases, it is imperative to reduce their etiological factors. Osteoporosis, being characterized by a sudden estrogen deficiency, may provide a favorable condition for bone metastasis. This work, using a humanized 3D in vitro model, aims at evaluating the relationship between osteoporosis and breast cancer‐derived bone metastases. Bone tissue discarded from total hip replacement surgery of healthy and osteoporotic patients was cultured in a rolling apparatus system in hypoxic environment. Protein levels (i.e., vascular endothelial growth factor (VEGF), VEGF receptor 1, VEGF receptor 2, interleukin (IL)‐6, IL‐1β, IL‐8 IL‐10, tumor necrosis factor α (TNF‐α), osteoprotegerin (OPG), receptor activator for nuclear factor KB ligand (RANKL)) and histological and immunohistochemical (i.e., cytokeratin 8 and 18) analyses showed a noticeable specificity of breast cancer cells for the colonization of osteoporotic bone. These data are the first to demonstrate that using humanized 3D in vitro systems, which individually model the pre‐ and postmenopausal bone microenvironment, it is possible to recognize major differences in tumor growth and colonization between healthy and osteoporotic status. Thus, this system might help to develop a shared system between basic and clinical sciences where a personalized diagnosis is associated to a therapeutic strategy designed for a single patient: a model able to achieve a translational research approach in the clinical setting, which may lead to the application and dissemination of personalized medicine. J. Cell. Physiol. 232: 1826–1834, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Humanized 3D in vitro model; relationship between osteoporosis and breast cancer‐derived bone metastases; differences in tumor growth and colonization between healthy and osteoporotic status.